The Communist Enemy and the 1943 Coup d’État.: Continuities in Repressive Classifications in the Context of the World War (Contenciosa, 2025)
This article analyzes the continuity of the «communist hypothesis», consolidated in 1941, in the conjectures about the internal enemy presented by the 1943 coup d’état. First, we address the characteristics of anti-communist repression deployed by various police agencies and its relationship to the organization of the Argentine Federal Police beginning in December 1943. Second, we analyze the discursive dimension of anti-communism, based on official government communication and press from nationalist right-wing sectors aligned with the dictatorship, in order to explore definitions of the «red problem» and its association with different issues, such as anti-fascism and other forms of activism accused of being communist.
Keywords: anti-communism, right-wing movements, repression, anti-fascism, Second World War